Enhancing Resilience and Reliability of Active Distribution Networks through Accurate Fault Location and Novel Pilot Protection Method - Lin Xu; Songhai Fan; Hua Zhang; Jiayu Xiong; Chang Liu; Site Mo (Energies, 2023)
The integration of distributed generation (DG) into the decentralized access of the distribution network transforms the existing structure into an active distribution network. The alteration in fault characteristics poses significant challenges to the coordinated operation of relay protection. Fault location within the distribution network plays a vital role in facilitating fault recovery and enhancing the resilience of the power system. It proves instrumental in improving the network’s ability to withstand extreme disasters, thereby enhancing the reliability of power distribution. Therefore, this paper provides a detailed analysis of the voltage fault components occurring during various fault types within an active distribution network. Building upon the identified characteristics of voltage fault components, a novel approach for the longitudinal protection of active distribution networks is proposed. This method involves comparing the calculated values of voltage fault components with their actual values. The proposed approach is applicable to various fault scenarios, including short-circuit faults, line break faults, and recurring faults. It exhibits advantages such as insensitivity to the penetration of distributed power supplies and robustness in withstanding transition resistance. The simulation results validate the effectiveness of the proposed method, affirming its applicability to diverse protection requirements within active distribution networks.